2023
DOI: 10.3390/ijms24065433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovocystatin on Amyloid β 1-42 Aggregation—In Vitro Studies

Abstract: Amyloid β peptides (Aβ) aggregating in the brain have a potential neurotoxic effect and are believed to be a major cause of Alzheimer’s disease (AD) development. Thus, inhibiting amyloid polypeptide aggregation seems to be a promising approach to the therapy and prevention of this neurodegenerative disease. The research presented here is directed at the determination of the inhibitory activity of ovocystatin, the cysteine protease inhibitor isolated from egg white, on Aβ42 fibril genesis in vitro. Thioflavin-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Aβ peptides have been identified as the cause of dendritic degeneration and loss of synapses, which ultimately leads to neuronal death in the rat hippocampus . Additionally, in vitro studies using cells from PC12 cells (rat pheochromocytoma , and SH-SY5Y cells) , (human neuroblastoma) have demonstrated that extracellular fibrillar aggregates of Aβ peptides are neurotoxic. However, these cells are unsuitable for neurodegenerative disease research due to their instability and inability to create a diverse population of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptides have been identified as the cause of dendritic degeneration and loss of synapses, which ultimately leads to neuronal death in the rat hippocampus . Additionally, in vitro studies using cells from PC12 cells (rat pheochromocytoma , and SH-SY5Y cells) , (human neuroblastoma) have demonstrated that extracellular fibrillar aggregates of Aβ peptides are neurotoxic. However, these cells are unsuitable for neurodegenerative disease research due to their instability and inability to create a diverse population of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptides have been identified as the cause of dendritic degeneration and loss of synapses, which ultimately leads to neuronal death in the rat hippocampus. 12 Additionally, in vitro studies using cells from PC12 cells (rat pheochromocytoma 14,15 and SH-SY5Y cells 16,17 (human neuroblastoma) have demonstrated that extracellular fibrillar aggregates of Aβ peptides are neurotoxic. However, these cells are unsuitable for neurodegenerative disease research due to their instability and inability to create a diverse population of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…With limited evidence for ovocystatin passage through the blood-brain barrier to the brain compartment, it is also possible that the observed effects were exerted peripherally and indirectly led to the changes in the brain tissue. In another study it was found that the use of ovocystatin in vitro led to reduced aggregation of 1-42 β-amyloid and in turn significantly decreased its toxicity in the PC12 cell line [ 115 ].…”
Section: Cystatin Cmentioning
confidence: 99%